2000
DOI: 10.1159/000045709
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Type IV Collagen as a Specific Indicator of the Progression of Diabetic Nephropathy

Abstract: Aims and Methods: This study was carried out to clarify whether the urinary excretion of type IV collagen (u-IV collagen) detected by specific radioimmunoassay, can be used as an indicator for the progression of diabetic nephropathy. Results: u-IV collagen was higher in diabetic subjects with microalbuminuria and overt proteinuria than those with normoalbuminuria, IgA nephropathy, membranoproliferative glomerulonephritis, membranous nephropathy, or control normal subjects. u-IV collagen was positively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
17
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
8
17
0
1
Order By: Relevance
“…27 Although type IV collagen is normally present only in the BM, we found that it was deposited in fibroblastic foci of UIP in a fine fibrillar pattern. These results agree with reports of type IV collagen deposition in certain pathologic fibrotic conditions such as cirrhotic livers, in the perisinusoidal area and fibrous septa; 28,29 diabetic nephropathy, in the mesangial matrix; 30 and tumor-related fibrotic lesions, in a fibrillar pattern but not in the BM. 31 We also found that type IV collagen was deposited around α-SMA-positive myofibroblasts in fibroblastic foci of UIP but not in the intraluminal buds of OP, and that TGF-β1 promoted the production of type IV collagen by cultured human lung fibroblasts together with increased expression of α-SMA in the fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…27 Although type IV collagen is normally present only in the BM, we found that it was deposited in fibroblastic foci of UIP in a fine fibrillar pattern. These results agree with reports of type IV collagen deposition in certain pathologic fibrotic conditions such as cirrhotic livers, in the perisinusoidal area and fibrous septa; 28,29 diabetic nephropathy, in the mesangial matrix; 30 and tumor-related fibrotic lesions, in a fibrillar pattern but not in the BM. 31 We also found that type IV collagen was deposited around α-SMA-positive myofibroblasts in fibroblastic foci of UIP but not in the intraluminal buds of OP, and that TGF-β1 promoted the production of type IV collagen by cultured human lung fibroblasts together with increased expression of α-SMA in the fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in intrarenal AngII activity was also shown to parallel the severity of fibrotic renal damage in chronic progressive nephropathy in rat (14) and human (15). In this study, urinary angiotensinogen levels were greater in patients with CKD, low eGFR, and high urinary excretion of protein and type IV collagen, a marker of renal extracellular matrix production (32,33), and correlated positively with renal AngII and type I collagen immunostaining intensities. It is conceivable that increased urinary angiotensinogen excretion in patients with low eGFR and high urinary type IV collagen excretion is due to enhanced angiotensinogen expression in the kidneys with progressive fibrosis, which is mediated by increased intrarenal AngII activity and results in progressive deterioration of renal function.…”
Section: Discussionsupporting
confidence: 60%
“…1,5 Studies which show increased urinary excretion of collagen IV (U CollagenIV ) in proteinuric diabetic patients suggest that urinary measurement of these proteins could reflect matrix changes and GBM damage in patients with diabetes. [6][7][8] Angiotensin-converting enzyme (ACE) inhibitors are known to have antiproteinuric effects on the diabetic kidney. 9 Recent studies indicate that the renoprotective effects of ACE inhibitors (ACE-Is) in diabetes could be at least partly independent of their blood pressure (BP)-lowering effects.…”
Section: Effects Of Ace Inhibition and Angiotensin II Receptor Blockamentioning
confidence: 99%